Clinical Nutrition: Recent Advances and Remaining Challenges - Bergheim, Ina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nutrition, often along with physical activity, is by now acknowledged as a cornerstone in the prevention and even more so the treatment of many diseases. Indeed, food and nutritional intake nowadays are often thought to be the main source of wellbeing sometimes over- but also underestimating the impact of nutritional intake, dietary pattern and food-derived natural compounds in their impact on human health. In this Special Issue entitled `Clinical Nutrition: Recent Advances and Remaining Challenges´ a broad overview and summary on recent findings in various fields of clinical nutrition with special focus on chronic and degenerative diseases like metabolic diseases, cancers, neurodegenerative diseases, inflammatory bowel diseases, sarcopenia but also malnutrition in elderly, infants and children is provided. Nutrition, often along with physical activity, is by now acknowledged as a cornerstone in the prevention and even more so the treatment of many diseases. Indeed, food and nutritional intake nowadays are often thought to be the main source of wellbeing sometimes over- but also underestimating the impact of nutritional intake, dietary pattern and food-derived natural compounds in their impact on human health. In this Special Issue entitled `Clinical Nutrition: Recent Advances and Remaining Challenges´ a broad overview and summary on recent findings in various fields of clinical nutrition with special focus on chronic and degenerative diseases like metabolic diseases, cancers, neurodegenerative diseases, inflammatory bowel diseases, sarcopenia but also malnutrition in elderly, infants and children is provided.